Unraveling the hydraulic properties of loess for landslide prediction: A study on variations in loess landslides in Lanzhou, Dingxi, and Tianshui, China - Gao-chao Lin; Wei Liu; Xing Su (China Geology)
ABSTRACT: Loess has distinctive characteristics, leading to frequent landslide disasters and posing serious threats to the lives and properties of local residents. The involvement of water represents a critical factor in inducing loess landslides. This study focuses on three neighboring cities sequentially situated on the Loess Plateau along the direction of aeolian deposition of loess, namely Lanzhou, Dingxi, and Tianshui, which are densely populated and prone to landslide disasters. The variations in hydraulic properties, including water retention capacity and permeability, are investigated through Soil Water Characteristic Curve (SWCC) test and hydraulic conductivity test. The experimental findings revealed that Tianshui loess exhibited the highest water retention capacity, followed by Dingxi loess, while Lanzhou loess demonstrated the lowest water retention capacity. Contrastingly, the results for the saturated permeability coefficient were found to be the opposite: Tianshui loess showed the lowest permeability, whereas Lanzhou loess displayed the highest permeability. These results are supported and analyzed by scanning electron microscopy (SEM) observation. In addition, the water retention capacity is mathematically expressed using the van Genuchten model and extended to predict unsaturated hydraulic properties of loess. The experimental results exhibit a strong accordance with one another and align with the regional distribution patterns of disasters.